Enhancing student athlete performance through an innovative aerobic gymnastics choreography model: evidence from Central Java - Fahmi, Donny Anhar; Herlambang, Tubagus; Wiyanto, Agus; Purwadi (Journal Sport Area, 2025)
Background: The decline in student participation in aerobic gymnastics at the Pekan Olahraga Pelajar Daerah (POPDA) or Regional Student Sports Week in Central Java highlights the need for more flexible and effective training methods. While video-based coaching offers promising flexibility, limited research has examined its impact on the performance of student athletes, particularly in choreographed aerobic routines. This study addresses that gap by testing a video-based choreography model tailored for young athletes. Research Objectives: This study aimed to evaluate the effectiveness of a student-focused aerobic gymnastics choreography model in enhancing performance, particularly in artistic and creative aspects. Methods: This quantitative experimental study involved 13 student athletes (elementary to high school level) who were selected from the POPDA Central Java event. A total sampling technique was applied. The athletes followed the choreographic model intervention, and performance scores—assessed by judges—were compared before and after the intervention using paired sample t-tests analyzed in SPSS 2022. Finding/Results: The results showed a statistically significant improvement in athlete performance following the application of the choreography model (p < 0.05). Improvements were most notable in artistic expression and movement creativity, highlighting the model's efficacy in developing aesthetic and technical skills. Conclusion: The specially designed aerobic gymnastics choreography model significantly enhances the performance of student athletes. The findings support the integration of video-based coaching as a complementary tool to traditional methods, offering flexibility in training and supporting long-term athlete development. This approach may be adopted by coaches and competition organizers to foster a more sustainable and competitive environment for aerobic gymnastics at both regional and national levels.